Simulated Learning in the Clinical Education of Novice Physiotherapy Students - Blackford, Julia; McAllister, Lindy; Alison, Jennifer (International Journal of Practice-based Learning in Health and Social Care, 2015)
Clinical simulation is well established in nursing and medical education. It provides an effective learning opportunity for students to develop confidence to apply their skills in the clinical setting. Using simulation in physiotherapy education is less well established. The aim of the pilot study reported on in this article was to determine if a simulated clinical experience for physiotherapy students could: 1) increase student confidence before commencing a traditional clinical placement; and 2) replace part of the traditional clinical placement without compromising the student’s ability to attain competency. The study consisted of replacing the first week of a five-week physiotherapy clinical placement with a simulated learning experience using standardised patients. Other structured learning activities such as peer learning, feedback sessions and opportunities for self-reflection were incorporated into the simulation week. Confidence to undertake clinical placement was measured at the beginning and end of the week and compared with a control group who undertook a five week traditional clinical placement. Assessment of student competence using the Assessment of Physiotherapy Practice, a standardised valid competency assessment tool, was compared between the two groups. Results indicated that the simulated learning experience significantly increased students’ confidence to apply their professional and clinical skills. One week of clinical simulation did not compromise students’ ability to achieve competency at the completion of their five-week placement. The power of the associated learning activities during the simulation week was evident from the students’ feedback. This study highlights the benefits of incorporating simulated learning experiences and well-structured learning activities as part of all clinical experiences.